Pedagogy of New Materialism: Advancing the Educational Inclusion Agenda for Children and Youth with Disabilities - Reddington, Sarah; Price, Deborah (Disability Studies Quarterly, 2018)
In advancing inclusion efforts this critical position paper makes explicit the relevance of new materialism as a pedagogy to counter the dominant medicalized models in Canadian and Australian school and community contexts. This paper argues the implementation of contemporary universal policies and programs do not adequately address the complex experiences of children and young people with disabilities. New materialism as a form of pedagogy, however, can prioritize individuals embodied, relational connections to all things and find new, creative ways to support young people with disabilities. The material turn is a welcoming pedagogical framework that places the material body and the emergent child at the center of educational and community practice.